Derivational network of the verb chingar in Mexican Spanish - Zacarías Ponce de León, Ramón F. (2025)
In this research, the analysis of the verb chingar and its derivatives through the model of derivational networks is shown, with the aim of studying the development of this concept and its derivative possibilities. The interest of this verb lies in the importance it has in Mexican culture, which is reflected in the large amount of secondary lexicon it has generated. A derivational network allows us to see the formal and semantic scope that a simple base word can have, first among the words that were generated directly in a first order of derivation, and then in those that were formed from these, in a second order of derivation. In the case of the verb chingar, from which the word chingón was directly derived, many words were formed from this adjective indirectly related to chingar in a second order of derivation. In this case, in the first order, eight derivatives were registered and in a second order, thirteen. These results stand out in a particular way because, according to the behavior that Díaz-Negrillo (2021) recorded for peninsular Spanish, it does not usually happen that verbs generate a greater amount of lexicon in a second order of derivation than in a first order, but rather it tends to be reduced . In this study we show the importance of considering neological lexicon in the construction of derivational networks.